The Emerald handbook of crime, justice and sustainable development - Blaustein, Jarrett; Fitz-Gibbon, Kate (Lecturer in criminology); Pino, Nathan; White, R. D. (Robert Douglas), 1956- (Bingley, U.K. : Emerald Publishing Limited, 2020)
The Emerald Handbook of Crime, Justice and Sustainable Development brings together a diverse and international collection of essays to critically examine issues relating to crime and justice in the United Nations 2030 Agenda for Sustainable Development. The United Nations 2030 Agenda for Sustainable Development provides an important global framework for advancing human rights, social justice and environmental sustainability. A number of the Agenda's Sustainable Development Goals (SDGs) address issues relating to crime, justice and security, and implicit in the 2030 Agenda is the assumption that members of the international community 'including traditional development actors and the myriad international, non-governmental, private, state and local organizations and actors that collectively contribute to the global governance of crime' must work together to enhance the capacities of both developing and developed countries to achieve this vision. Against this backdrop, this volume analyses and interrogates the SDGs from different theoretical and ideological standpoints originating from within and beyond criminology, illustrating the complex and politically contentious nature of these issues and providing insight into the different possibilities that exist for realising the SDGs and mitigating the risk that initiatives meant to realise the SDGs, may in fact contribute to harmful and counterproductive policies and practices. This book will be essential reading for scholars and students within criminology, criminal justice, socio-legal studies, international relations and development studies.
Part 1: Contextualising the Crime Development Nexus Chapter 1: The Nexus between Crime, Justice and Sustainable Development; Jarrett Blaustein, Kate Fitz-Gibbon, Nathan W. Pino and Rob White. -- Chapter 2: Governing the Crime-Development Nexus: A Historical Perspective; Jarrett Blaustein, Tom Chodor and Nathan W. Pino. -- Chapter 3: Responding to Organized Crime through Sustainable Development: Tensions and Prospects; Sasha Jesperson. -- Chapter 4: A Marxist Perspective on the 2030 Agenda for Sustainable Development; Valeria Vegh Weis and Rob White. Part 2: Facilitating Orderly Development -- Chapter 5: Violence Reduction and Sustainable Development: Challenging the Violence Divide; Elliott Currie. -- Chapter 6: Corruption Reduction as a Target of the Sustainable Development Goals: Applying Indicators and Policy Frameworks; Kempe Ronald Hope.Sr. -- Chapter 7: Problematizing the Rule of Law Agenda in the SDG Context; Danielle Watson, Ariel Yap, Nathan W. Pino and Jarrett Blaustein. -- Chapter 8: Polycentric Security Governance and Sustainable Development in the Global South; Julie Berg and Clifford Shearing. -- Chapter 9: The Emperor's New Clothes: A Critical Reading of the Sustainable Development Goals to Curb Crime and Violence in Latin America; Manuel Iturralde. -- Chapter 10: Development and the Externalization of Border Controls; Ana Aliverti and Celine Tan. Part 3: Social Justice for Sustainable Development -- Chapter 11: Inclusive and Safe Cities for the Future: A Criminological Analysis; Diana Rodriguez-Spahia and Rosemary Barberet. -- Chapter 12: Measuring peace, justice and inclusion: Security sector reform and sustainable development; Eleanor Gordon. -- Chapter 13: Youth Justice as Justice for Children: Towards a Capabilities Approach; Katherine S. Williams and Heddwen Daniels. -- Chapter 14: Technology, Domestic Violence Advocacy, and the Sustainable Development Goals; Bridget Harris, Molly Dragiewicz and Delanie Woodlock. -- Chapter 15: Eliminating all forms of violence against all women and girls: some criminological reflections on the challenges of measuring success and gauging progress; Kate Fitz-Gibbon and Sandra Walklate. Part 4: Transnational Crime, Global Threats and Sustainable Development -- Chapter 16: Examining the Promise and Delivery of Sustainable Development Goals in Addressing Human Trafficking and Modern Slavery; Sanja Milivojevic, Bodean Hedwards and Marie Segrave. -- Chapter 17: Following the Money: Illicit Financial Flows and Sustainable Development Goal 16.4; Liz Campbell and Nicholas Lord. -- Chapter 18: Global Drug Policy and Sustainable Development: An Uneasy Relationship; Summer Walker. -- Chapter 19: Sustainable Development, Counter-Terrorism and the Prevention of Violence Extremism: Right-Wing Nationalism and Neo-Jihadism in Context; Imogen Richards. -- Chapter 20: Global Trade in Stolen Culture and Nature as Neocolonial Hegemony; Simon Mackenzie, Annette Hübschle and Donna Yates. Part 5: Environmental Justice for Sustainable Future -- Chapter 21: A Paradox of 'Sustainable Development': Critique of the Ecological Order of Capitalism; John E. McDonnell, Helle Abelvik-Lawson and Damien Short. -- Chapter 22: Access to Safe and Affordable Drinking Water as a Fundamental Human Right: The Case of the Republic of Slovenia; Katja Eman and Gorazd Meško. Chapter 23. A Review of Responses to IUU Fishing Around the World through the Lens of Situational Crime Prevention; Nerea Martaeche, Monique C. Sosnowski and Gohar A. Petrossiam. Chapter 24. The Sustainable Development Goals Link to Human Security: An Exploration of Illegal Logging in Vietnam; Anh Ngoc Cao and Tanya Wyatt. Chapter 25. Air Pollution, Climate Change and International (In) Action; Reece Walters. Chapter 26. Taking Urgent Action to Combat Climate Change and its Impacts: A Criminological Perspective; Ronald C. Kramer and Rob White.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Criminal justice, Administration of; Sustainable development; Social Science -- Criminology; Crime & criminology